Estratégias de construção no cinema de Andriêi Tarkóvski: a perspectiva inversa como procedimento - Jallageas, Neide (2007)
This thesis proposes to study the strategies of construction of the Russian (Soviet) filmmaker Andriêi Arsiénievitch Tarkóvski, establishing as the scope of the analysis the seven full-length features he made between 1962 and 1986. The central hypothesis is that the Tarkovskian cinematic works were made through the articulation of procedures inherent to the world view model organized through an reverse perspective, an articulation which opened possibilities for aesthetic experimentations associated to the predominant model, organized by the linear perspective. The underlying hypothesis is that the construction strategies in Tarkóvsky s cinema present themselves as a form o resistance to the Soviet cannons of arts and communication. The primary objective is to understand how these world view models connect with the visible world to produce visual messages and in which way such models problematize the concept of realism in the Arts and one of its derivatives, the Socialist Realism. The secondary objective is to discuss the procedures that intersect in time and space in distinct constructions: the Russian Avant-Gardes, medieval painting and Andriêi Tarkóvski s cinema. The final objective is to demonstrate how associative models dynamized the construction of this cinema through the use of the reverse perspective as a procedure, counterposing itself to the cannons established by the Socialist Realism. The theoretical basis of this research lies on the studies of the dialogical processes realized by the Russian theorist Mikhail Bakhtin, especially regarding his concepts of Small and Great Time, Chronotopy and Active Comprehension, in dialog with the manifests and writings of the Russian Avant- Gardes, taking mainly into perspective the conceptual field worked by the Russian thinker Pável Floriênski concerning the Reverse Perspective, and with the thoughts of Gilles Deleuze about the Ritornello. Methodologically, sequences of the seven fulllength features are selected in light of the concepts in which this work is based on. From these sequences the paradigms that trigger the association between the world view models have been highlighted: the potential lines that connect spaces; the formation of multiple centers and the densening of the centres or chronotopical extracts. Finally, this study stands out as it contributes to the problematization of guiding models of the totalitarian aesthetics that direct artistic and communicational creation and others, that direct strategies that aim at resisting artistic and communicational totalitarianism nowadays